Strain Gauge: study of strain distributions around three Morse taper prosthetic connections with offset positioning in machined and plastic copings under vertical load - Santos, Vivian Mayumi Miyazaki; Sousa, Talitha de Cássia Silva; Louzada, Frederico Freire; Nishioka, Gabriela Nogueira de Melo; Nishioka, Renato Sussumu (Brazilian Dental Science, 2012)
The aim of this study was to evaluate through strain gauge the strain distribution occurred around 3 Morse taper implants with positioning offset, by varying the types of copings: plastic and machined. Microunit prosthetic abutments were connected onto the implant platforms. Ten frameworks composed of 3 copings were casted in cobalt-chromium alloy as single block (Co-Cr). Half of the copings were machined (n=5) and half were made of plastics (n=5). Four strain gauges were placed into the polyurethane block tangential to the 3 implants. The frameworks were fixed at their respective sites with the aid of a retaining screw with torque of 20 N.cm, achieve with a mechanical torquemeter. The vertical load of 30 Kg was applied through a spherical point of 2 mm diameter for 10 s, onto each one of the 3 screws of the framework through a device for load application The records of the strain reading were submitted to ANOVA and Tukey tests (5%). There were statistically significant differences (p=0.0174) between the coping type used (machined and plastic). The micro strain mean values were: point C at the machined coping 282.5 ?m (±120.8), point B at the machined coping 229.5 ?m (±76.1), point A at the machined coping 209.8 ?m (±55.0), point C at the plastic coping 155.0 ?m (±30.5), point B at the plastic coping 146.2 ?m (±25.8) and point A at the plastic coping 130.36 ?m (±21.83). It was concluded that there was a significant difference between the coping types, once the plastic coping exerted smaller micro strain on Morse taper implants than the machined copings.